Extinction in Two-Species Nonlinear Discrete Competitive System - Liqiong Pu; Xiangdong Xie; Fengde Chen; Zhanshuai Miao (Discrete Dynamics in Nature and Society)
We propose a nonlinear discrete system of two species with the effect of toxic substances. By constructing a suitable Lyapunov-type function, we obtain the sufficient conditions which guarantee that one of the components will be driven to extinction while the other will be globally attractive with any positive solution of a discrete equation. Two examples together with their numerical simulations illustrate the feasibility of our main results. The results not only improve but also complement some known results.